Effects of Tetraselmis chuii Microalgae Supplementation on Ergospirometric, Haematological and Biochemical Parameters in Amateur Soccer Players - Toro, Víctor (Int J Environ Res Public Health, 2020)
This study aimed to analyse the effects of Tetraselmis chuii (TC) microalgae supplementation during thirty days on ergospirometric, haematological and biochemical parameters in amateur soccer players. Thirty-two amateur soccer players divided into a control group (CG; n = 16; 22.36 ± 1.36 years; 68.36 ± 3.53 kg) and a supplemented group (SG; n = 16; 22.23 ± 2.19 years; 69.30 ± 5.56 kg) participated in the double-blind study. SG ingested 200 mg of the TC per day, while CG ingested 200 mg per day of lactose powder. Supplementation was carried out for thirty days. The participants performed a maximal treadmill test until exhaustion. The ergospirometric values at different ventilatory thresholds and haematological values were obtained after the test. Heart rate decreased after supplementation with TC (p < 0.05). Oxygen pulse, relative and absolute maximum oxygen consumption increased in SG (pre vs. post; 19.04 ± 2.53 vs. 22.08 ± 2.25; 53.56 ± 3.26 vs. 56.74 ± 3.43; 3.72 ± 0.35 vs. 3.99 ± 0.25; p < 0.05). Haemoglobin and mean corpuscular haemoglobin increased in SG (pre vs. post; 15.12 ± 0.87 vs. 16.58 ± 0.74 p < 0.01; 28.03 ± 1.57 vs. 30.82 ± 1.21; p < 0.05). On the other hand, haematocrit and mean platelet volume decreased in SG (p < 0.05). TC supplementation elicited improvements in ergospirometric and haematological values in amateur soccer players. TC supplementation could be valuable for improving performance in amateur athletes.